Elevated Serum IGFBP-2 and CTGF Levels Are Associated with Disease Activity in Patients with Dermatomyositis. (20th March 2022) - Yang, Min; Chen, Yuehong; Yin, Geng; Lin, Sang; Liu, Huan; Huang, Yupeng; Tian, Yunru; Zhou, Yueyuan; Luo, Fengming; Xie, Qibing
Abstract : Background. Insulin-like growth factor-binding proteins (IGFBPs) and connective tissue growth factor (CTGF) participate in angiogenesis. Dermatomyositis (DM) is characterized by microvasculopathy-derived skin lesions. Here, we investigated the clinical significance of serum IGFBP and CTGF levels in DM patients. Methods. In this study, 65 DM patients and 30 healthy controls were enrolled. Serum IGFBP and CTGF levels were examined by ELISA, and their correlation with clinical and laboratory findings was analyzed by Spearman's correlation. Results. Serum IGFBP-2, IGFBP-4, and CTGF levels were higher in DM patients than in healthy controls (median (quartile): 258.9 (176.4–326.1) ng/mL vs. 167.7 (116.1–209.4) ng/mL, p < 0.0001 ; 450.4 (327.3–631.8) ng/mL vs. 392.2 (339.0–480.2) ng/mL, p = 0.04 ; and 45.71 (38.54–57.45) ng/mL vs. 35.52 (30.23–41.52) ng/mL, p = 0.001, respectively). IGFBP-2 and CTGF levels were positively correlated with cutaneous (r = 0.257, p = 0.040 and r = 0.427, p = 0.015, respectively) and global (r = 0.380, p = 0.002 and r = 0.292, p = 0.019, respectively) disease activity in DM patients. Conclusion. Serum IGFBP-2 and CTGF levels were increased in patients with DM and correlated with cutaneous and global disease activity.